2020
DOI: 10.1186/s12935-020-01318-4
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circUBAP2 regulates proliferation and invasion of osteosarcoma cells through miR-641/YAP1 axis

Abstract: Background: Osteosarcoma (OS) is a common malignant bone cancer and is still a growing threat to young people. Circular RNAs (CircRNAs) are reported to be involved in the development of diverse human cancers. However, the role of circUBAP2 in OS progression is rarely reported. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to detect the expression levels of circUBAP2 and miR-641 in OS tissues and cells. Cell Counting Kit-8 (CCK-8) assay was employed to check cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…circUBAP2 modulates pancreatic adenocarcinoma tumorigenesis by regulating the levels of hsa-miR-494 and the expression of CXCR4, HIF1A, ZEB1, SDC1, and TWIST1 32 . In addition, circUBAP2 modulates cancer cell malignancy through the miR-641/YAP1 axis and miR-361-3p/SOX4 axis in osteosarcoma and cervical cancer, respectively 33 , 34 . Consistently, our results showed that circUBAP2 silencing was sufficient to attenuate HCC cell migration, as well as the promotive effects of CXCL11 on HCC cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…circUBAP2 modulates pancreatic adenocarcinoma tumorigenesis by regulating the levels of hsa-miR-494 and the expression of CXCR4, HIF1A, ZEB1, SDC1, and TWIST1 32 . In addition, circUBAP2 modulates cancer cell malignancy through the miR-641/YAP1 axis and miR-361-3p/SOX4 axis in osteosarcoma and cervical cancer, respectively 33 , 34 . Consistently, our results showed that circUBAP2 silencing was sufficient to attenuate HCC cell migration, as well as the promotive effects of CXCL11 on HCC cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, YAP1 knockdown inhibited OS cell proliferation in vitro and in vivo. [19][20][21][22] In addition, upregulation of YAP1 promoted OS cell proliferation, migration, and invasion, thereby leading to tumorigenesis. 23 TRPS1 is also generally overexpressed in multiple types of cancer [11][12][13]24,25 and our previous study has confirmed its role in enhancing drug resistance in OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a dual‐luciferase reporter assay shows circRNA UBAP2 is can bind to miR‐641 (Gong et al 2020a,b), which can decrease the expression of YAP1 (H. Wu et al, 2020), a transcriptional co‐activator involved in cancer progression (Vincent‐Mistiaen et al, 2018). Transfection experiment shows overexpression YAP1 will enhance the proliferation and invasion ability of OS cells (G. Liu et al, 2018), reversing E‐cadherin and Vimentin protein levels of miRNA‐641 group (H. Wu et al, 2020) as well. Besides this, sponged by circRNA UBAP2, miR‐506‐3p is reported to work as an inhibitor of SEMA6D (Gong et al 2020a,b), which functions as an oncogene in OS with the ability to promote the proliferation, invasion, and migration of OS cells (Kansara et al, 2014).…”
Section: Circrna Regulation Of Mirna In Osteosarcomamentioning
confidence: 99%